Managing and monitoring sustainable regional devolopment in alpine regions - Roland Scherer; Klaus-Dieter Schnell; Adrian Berwert; Thomas Bieger; Heinz Ritter (European Regional Science Association (ERSA), 2002)
Alpine landscape always has been affected by human economic activities. Traffic economy, tourism economy and industrial structure dominated by small and medium-sized enterprises have been the drivers of economy development as well as of changes in the alpine landscape throughout the last century. There have been tremendous influences of economic activities on special areas but also on the alpine landscape in general. For years numerous regions have been subjected to a strong structural change. Globalisation leads to an acceleration of this structural change. Also, globalisation leads to a fast transition of companies, branches and economies. This transformation is determined by the conversion of the core elements of economic activities, single companies. Companies and branches of the alpine economy have been affected heavily by this transformation process due to several reasons (former regulation, decline of transport costs, etc.). The regions try to influence the negative effects of this structural change in various ways. The results of their efforts are very different. Some regions manage to improve their economic situation whereas others get worse. It is an open question, which structural and procedural factors are responsible for these differences. There could be a gap between wishful thinking in policy making /development of regional strategies and the possibilities of economic development. All participation processes and works on regional strategies have to be based on a sound understanding of the possibilities to influence the economic development. Regional development has tremendously changed in the past few years. So, the question arises how regions are going to organise and manage their sustainable development in the long run. Therefore, appropriate management tools have to be designed. However the central question of the paper is, how regions manage to remain as attractive living spaces. If we knew, what strategies regions should apply and how they should change their strategies in the light of the growing influence of globalisation, we could be able to develop tools for future regional development, that could take the demands of sustainability better into account. Therefore, the paper focuses on the following four areas: - The long-term changes of the (economic) situation in peripheral regions of the Alps. What have been the most important sources of income/net value creation in the last years? How have factors like income, branches and work force developed? How has the created income and value been distributed to different branches and population groups - The effects of globalisation on relevant branches for peripheral regions (e.g. Tourism, agriculture and forestry, building and industry). Which effects of globalisation have been the most influential ones? What external effects have to be expected in alpine regions through these economic trends? - Evaluation of the regional strategies to cope with economic structural changes. It will be promising to examine the Regional Development Schemes. - Development of a management system for sustainable regional development in peripheral regions, which should be applicable as a standardized tool.
Keywords: 330